Agnoletti, Mauro (2018). Storia del bosco. Il paesaggio forestale italiano - Zanolin, Giacomo (Documents d’Anàlisi Geogràfica, 2020)
Agnoletti, Mauro (2018) Storia del bosco. Il paesaggio forestale italiano Bari y Roma: Laterza, 266 p. ISBN 9788858132548